Short-chain chlorinated paraffins in cooking oil and related products from China. (November 2015) - Cao, Yang; Harada, Kouji H.; Liu, Wanyang; Yan, Junxia; Zhao, Can; Niisoe, Tamon; Adachi, Ayumu; Fujii, Yukiko; Nouda, Chihiro; Takasuga, Takumi; Koizumi, Akio
Highlights: SCCPs were detected in cooking oil, fried food, and raw seeds from Chinese cities. Cooking oil contained SCCP concentrations of <9–7500 ng g −1 . Estimated total SCCP intake in cooking oil for a Chinese person was <0.78–38 μg d −1 . Cooking oil and fried food could be the sources of SCCPs to Chinese people. Abstract: Short-chain chlorinated paraffins (SCCPs) are emerging persistent organic pollutants. It has been found that dietary intakes of SCCPs in China have recently increased and are now higher than in Japan and Korea. The contribution of cooking oil to dietary exposure to SCCPs in China was evaluated by analyzing SCCPs in cooking oil, raw seeds used to produce cooking oil, and fried confectionery products collected in China in 2010 and 2012. Detectable amounts of SCCP homologs were found in 48 out of the 49 cooking oil samples analyzed, and the SCCP concentrations varied widely, from <9 to 7500 ng g −1 . Estimated dietary intakes of total SCCPs in cooking oil ranged from <0.78 to 38 μg d −1 . The estimated dietary intake of SCCPs was relatively high (mean 14.8 μg d −1 ) for residents of Beijing. Fried confectionery was found to contain SCCP concentrations of 11–1000 ng g −1 . Cooking oil might therefore be one of the sources of SCCPs to Chinese diets. SCCPs were also detected in raw seeds used to produce cooking oil, but the concentrations varied widely. The SCCP homolog patterns in the raw seed and cooking oil samples were different, implying that the seeds used to produce the oil (and therefore the soil on which the seeds were produced) were unlikely to be the sources of SCCPs in cooking oil. Further investigations are needed to determine the routes through which cooking oil becomes contaminated with SCCPs during the production and processing of the oil.